Transformações socioambientais e ecologia da paisagem nas microbacias urbanas de Altamira - Pará - COSTA, Vagner Nascimento (Universidade Federal do Pará, 2023)
The urban space must be understood in a dynamic perspective having as reference the growth of the city. In terms of environmental issues, the disorderly growth associated with the inexperience of environmental and territorial planning incurs in the formation of socioenvironmental problems and in the restructuring of the landscape. Through mathematical modeling and geographic data, it is possible to understand the processes that operate between social and cultural environments and the available natural resources. Associated to the geoprocessing technologies, the landscape metrics are valuable tools in Landscape Ecology to measure changes in a area of study by establishing temporal assessments of the modification of landscape fragments, through the evaluation of criteria and establishment of propositions that allow understand the transformation capacity of the territory. The general objective of the present research is to understand the socio-environmental and ecological transformations of the landscape in the urban watersheds of Altamira/PA, enabling the formulation of a prognostic scenario to support the environmental urban planning process through spatial assessment and application of landscape metrics to the forest fragments related to the municipal urban perimeter, considering the time periods of 2000, 2010 and 2020.